TINDAK PIDANA TERORISME DAN UPAYA PENCEGAHAN MELALUI DERADIKALISASI - Saragih, Yasmirah Mandasari; Ndruru, Restika; Mulyadi, Mus; Ibrahim, Ibrahim (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The crime of terrorism is an act that uses violence or the threat of violence to create an atmosphere of terror or fear on a widespread basis, aimed at people or groups of people, or damaging public facilities with ideological, political, or security objectives. Terrorism is characterized as an unlawful act committed systematically with the aim of destroying or disrupting the sovereignty of the nation and state. This means that terrorism is not just an ordinary crime but also has ideological or political goals and is carried out by means of violence that makes people feel afraid or panic. Law of the Republic of Indonesia Number 5 of 2018 on the Amendment to Law Number 15 of 2003 on the Eradication of the Criminal Acts of Terrorism provides a more detailed definition of the criminal act of terrorism, including various acts of preparation, attempt, assistance, and the execution of the terrorist act itself. There are various forms of acts of terrorism in Indonesia and there are efforts to prevent criminal acts of terrorism, namely through deradicalization, which is a proactive step and requires caution with consideration of the plurality of Indonesian society and the vulnerability of plurality to social conflict in society.